2D Ultrathin p‐type ZnTe with High Environmental Stability - Shengdong You; Zhen Wu; Lijuan Niu; Xiaohong Chu; Yihong She; Zhenjing Liu; Yuting Cai; Hongwei Liu; Lijie Zhang; Kenan Zhang; Zhengtang Luo; Shaoming Huang (Advanced Electronic Materials, 2022)
Abstract The poor air stability hinders the practical application of most 2D materials. P‐type 2D ZnTe has drawn widespread attention, thanks to its wide direct bandgap and outstanding environmental stability. However, the controllable synthesis of ultrathin 2D ZnTe remains a huge challenge due to the intrinsic unlayered crystal structure. Here, p‐type 2D ultrathin ZnTe flakes are controllably synthesized by using space‐confined physical vapor deposition. In situ temperature‐dependent Raman and electronical measurements show the thermal stability up to 420 K and outstanding air stability even under humidity of 95%. The ZnTe flakes‐based photodetector demonstrates the broadband response varying from the visible to near infrared region, responsivity of 18.3 A W‐1 and detectivity (D*) of 2.89 × 109 Jones under 405 nm illumination, implying promising potential application in electronics and optoelectronics worked in harsh environment.